2016
DOI: 10.1097/iae.0000000000000732
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Epiretinal Membrane Surgery in Young Children

Abstract: Even in very young children, surgery resulted in a significant long-term improvement. Children screening was essential for diagnosis and treatment in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…However, during the follow-up, spontaneous relief of the traction caused by the ERM was observed, with improvement in VA. That suggests that early surgery in selected cases could be of benefit in terms of recovery of VA, which have been concluded in some other works [9, 11, 12]. …”
Section: Discussionsupporting
confidence: 63%
“…However, during the follow-up, spontaneous relief of the traction caused by the ERM was observed, with improvement in VA. That suggests that early surgery in selected cases could be of benefit in terms of recovery of VA, which have been concluded in some other works [9, 11, 12]. …”
Section: Discussionsupporting
confidence: 63%
“…[10][11][12][13][14] While surgical management in pediatric cases remains controversial, ERM peel to relieve vitreomacular traction in CHRRPE has been reported to improve visual function in select patients. 11,15,16 To our knowledge, only 4 cases of histopathologic evaluation of ERM overlying CHRRPE following vitrectomy have been reported to date, [17][18][19] likely given limitations in specimen handling, processing, and analysis. Unlike the case by Almony and colleagues, 17 no RPE cells were identified in our specimen.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although observation of NF2-related epiretinal membranes is an option if the vision loss is mild, recent studies have shown gains in vision with early pars plana vitrectomy and epiretinal membrane peel. 6,7 Bonnin et al 7 reported operating on 13 patients with epiretinal membranes who were 12 years or younger. Of the 13 patients, 12 had improvement in visual acuity and the corrected visual acuity improved from an average of 20/160 to 20/40.…”
Section: Discussionmentioning
confidence: 99%